Clonal selection in the human Vδ1 T cell repertoire indicates γδ TCR-dependent adaptive immune surveillance - Davey, Martin S. (Nat Commun, 2017)
γδ T cells are considered to be innate-like lymphocytes that respond rapidly to stress without clonal selection and differentiation. Here we use next-generation sequencing to probe how this paradigm relates to human Vδ2(neg) T cells, implicated in responses to viral infection and cancer. The prevalent Vδ1 T cell receptor (TCR) repertoire is private and initially unfocused in cord blood, typically becoming strongly focused on a few high-frequency clonotypes by adulthood. Clonal expansions have differentiated from a naive to effector phenotype associated with CD27 downregulation, retaining proliferative capacity and TCR sensitivity, displaying increased cytotoxic markers and altered homing capabilities, and remaining relatively stable over time. Contrastingly, Vδ2(+) T cells express semi-invariant TCRs, which are present at birth and shared between individuals. Human Vδ1(+) T cells have therefore evolved a distinct biology from the Vδ2(+) subset, involving a central, personalized role for the γδ TCR in directing a highly adaptive yet unconventional form of immune surveillance.